2013
DOI: 10.1590/s0100-69162013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and crop coefficients of melon plants measured by lysimeter and estimated according to FAO 56 methodology

Abstract: Aiming at contributing to an adequate management of water resources, this study aimed to analyze and compare evapotranspiration (ETc) and crop coefficients (Kc) of melon plants measured by a lysimeter and estimated according to the FAO 56 methodology, in the city of Mossoró, state of Rio Grande do Norte (RN), Brazil. In order to measure ETc, weighing lysimeters with an area of 2.25m 2 were used, with two repetitions. The Penman-Monteith equation parameterized by FAO was used to estimate the reference evapotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
6
0
2
Order By: Relevance
“…From the twentieth day after sowing, the Kcb BREB related well Allen et al (1998), Melo et al (2013) and Miranda et al (1999). Shrestha and Shukla (2014), who investigated watermelon plants grown on plastic mulch and observed that Kcb followed the increase in fc and transpiration increased with plant growth, becoming the main component of the ETc.…”
Section: Melon Etc and Basal Crop Coefficientssupporting
confidence: 76%
See 1 more Smart Citation
“…From the twentieth day after sowing, the Kcb BREB related well Allen et al (1998), Melo et al (2013) and Miranda et al (1999). Shrestha and Shukla (2014), who investigated watermelon plants grown on plastic mulch and observed that Kcb followed the increase in fc and transpiration increased with plant growth, becoming the main component of the ETc.…”
Section: Melon Etc and Basal Crop Coefficientssupporting
confidence: 76%
“…Miranda et al (1999) reported for the initial phase a Kc of approximately 0.2 and a mid-season Kc value > 1.0 under conditions without plastic mulch. Melo et al (2013) reported a 30 % underestimation of Kcb FAO compared with Kcb by lysimeter measurements. These authors suggested that the plastic mulch favored the increase in plant transpiration, which explains the much higher Kc value.…”
Section: Melon Etc and Basal Crop Coefficientsmentioning
confidence: 93%
“…A number of research studies were performed with mulch, mainly plastic sheets (Carvalho et al, 2012;Melo et al, 2013;Shukla et al, 2013Shukla et al, , 2014Zheng et al, 2013;Biswas et al, 2015;Borges et al, 2015;Yang et al, 2018;Zhang et al, 2018). Their effect was not considered since this review does not refer to the periods before the mid-season when impacts of mulch in lowering E s are greater.…”
Section: Fruit and Pod Vegetable Cropsmentioning
confidence: 99%
“…The coefficient of determination 0.8329 show a good adjustment between rates for Kc, enhancing the relevance of the referred to results for sugar cane irrigation management in the savannah region. Melo et al (2013) report that variations in Kc rates at short time intervals are caused by microclimate variations, differential growth of the plants, measurement mistakes due to hysteresis caused by the addition of water and by the loss of irrigation water by evaporation, expansion and contraction caused by temperature variations during the day, and other factors.…”
Section: Crop Coefficient For Sugar Canementioning
confidence: 99%